2019
DOI: 10.1177/1747021819839668
|View full text |Cite
|
Sign up to set email alerts
|

Self-related shapes can hold the eyes

Abstract: Increasing evidence suggests that individuals are highly sensitive to self-related stimuli. Here, we report two experiments conducted to assess whether two schematic stimuli, arbitrarily associated with either the self or a stranger, can shape attention holding in an oculomotor task. In both experiments, participants first completed a manual matching task in which they were asked to associate the self and a stranger with two shapes (triangle vs. square). Then, in an oculomotor task, they were asked to perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 44 publications
(113 reference statements)
2
26
1
2
Order By: Relevance
“…The results showed that if the pairings were matching, then participants were faster to judge self-associated than friend-or stranger-associated stimuli, suggesting that participants demonstrated a "self-prioritization effect" for arbitrary rapidly self-associated geometrical shapes. This effect was later replicated with geometrical shapes [22][23][24][25][26][27][28][29][30][31][32][33][34], other kinds of visual stimuli, such as Gabor patches [35], tilted lines [36], images of food [37], avatars [38], and faces [20,39], as well as with stimuli in other sensory modalities [40][41][42].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The results showed that if the pairings were matching, then participants were faster to judge self-associated than friend-or stranger-associated stimuli, suggesting that participants demonstrated a "self-prioritization effect" for arbitrary rapidly self-associated geometrical shapes. This effect was later replicated with geometrical shapes [22][23][24][25][26][27][28][29][30][31][32][33][34], other kinds of visual stimuli, such as Gabor patches [35], tilted lines [36], images of food [37], avatars [38], and faces [20,39], as well as with stimuli in other sensory modalities [40][41][42].…”
Section: Introductionmentioning
confidence: 82%
“…While our focus was on dissociation of top-down and bottom-up mechanisms, other studies focused on different aspects of self-prioritization. For example, several recent studies have investigated whether arbitrary self-association affects processes related to spatial attention in a visual search task [36,71] and in a spatial cuing tasks [21,33], finding evidence that only in specific contexts can such modulation take place. Other studies have investigated whether self-associated stimuli have privileged access to consciousness, but have found inconsistent results ( [72] vs [35,73]).…”
Section: Plos Onementioning
confidence: 99%
“…The present study is also embedded in a recent stream of oculomotor research in which relevant factors are manipulated within the same block of trials on the one hand, or in different blocks on the other hand (e.g., Dalmaso, Castelli, & Galfano, 2019;Dalmaso, Castelli, & Galfano, 2020c;Zeligman & Zivotofsky, 2017). One specific manner in which this goal can be achieved is by manipulating experimental instructions in such a way that the participants are forced to adopt either a broad or a narrow attentional set depending on whether their knowledge about a taskrelevant feature (e.g., the direction of the instructed saccade or the target location) is kept constant within a block of trials or changes unpredictably from trial to trial.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental psychology, spatial cuing tasks represent an established paradigm to measure the impact of self-relevance on cognitive information processing (Alexopoulos et al, 2012; Dalmaso et al, 2019; Sui et al, 2009; Wójcik et al, 2018). These tasks consist of responding to targets which appear at locations that are either cued by a stimulus of interest (valid trials) presented shortly before the target (i.e., with a short stimulus-onset asynchrony [SOA], ≤ 200 ms) or not (invalid trials).…”
mentioning
confidence: 99%
“…Remarkably, the self-associated arrow was more efficient in guiding attention than the friend-associated arrow (see Zhao et al, 2015, for limitations of this effect). Likewise, in an oculomotor task, saccades toward targets positioned away from self- versus other-associated shapes were initiated more slowly (Dalmaso et al, 2019). In visual search, the cuing of target locations by new self-associated stimuli enhanced target detection in some studies (Wade & Vickery, 2018), but not in others (Siebold et al, 2015).…”
mentioning
confidence: 99%